The Effect of Workplace Tele-pressure On Psychological Well-being among Academic in El Azhar University through the Moderation Role of Psychological Hardiness - Aboseif, Rasha (The Arab Journal of Administration, 2022)
dr_rashaseif@azhar.edu.eg The study aimed to identify the impact of the Workplace TeLe-pressure on psychological well-being, through the interactive of psychological Hardiness. Among the faculty members of Al-Azhar University–Asyut. This study was conducted on a sample size reached (384), the number of valid lists on which the statistical analysis was conducted (280) list with a response rate of (73%). The most important results of the study are proving the interactive role of the variable of psychological Hardiness and its dimensions (commitment and control) in the relationship between the Workplace TeLe-pressure and psychological well-being. In light of the results, a group of recommendation was developed.